Evidências empírico-exploratórias de fatores críticos de sucesso em treinamentos corporativos a distância via web - Lima, Nelson Cirne Casado (2006)
The goal of this dissertation is to identify some of the relevant elements that are related to corporate in-house training programs via the worldwide web. An analysis of the way these factors act upon the success of these processes was conducted. To complete this assignment, one real case was studied using the methodology proposed and which in itself was actually used by an insurance company. The results obtained suggest that some components influence the accomplishment of this procedure. According to the results verified, they do bring a set of observations that must be considered by companies in their implementation strategies of this kind of training program.